Juan Andrés: una visión ilustrada del teatro grecolatino - López Fonseca, Antonio (Revista de Filología Alemana, 2010)
This article aims to approach the re-classification of non-artistic prose from the eruditeencyclopaedic perspective which characterizes the Spanish Enlightenment. The outstanding work of Juan Andrés’ Del origen, progresos y estado actual de toda la literatura (1782- 1799) can clearly be incorporated into this framework. This study explores the presence of Greek and Roman literatures in the text and, most specifically, the vision offered by the Jesuit of Greco-Latin theatre.